PERAN STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS PSIKOLOGI HUMANISTIK DALAM PENGUATAN KECERDASAN SPIRITUAL SISWA - Febry Irwansyah Pasaribu; Muslim Afandi; Mhd Subhan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Spiritual intelligence is increasingly recognized as a crucial dimension in contemporary education, particularly amid rapid social change and technological advancement that may shift students’ value orientations. The phenomenon of moral degradation and the dominance of cognitively oriented instruction underscore the urgency of pedagogical transformation capable of integrating affective and spiritual dimensions in a more meaningful way. This study aims to examine the role of Islamic Religious Education learning strategies based on humanistic psychology in fostering students’ spiritual intelligence through a qualitative approach employing a library research design. Data were collected through an extensive review of relevant literature, encompassing diverse theoretical and conceptual perspectives that reflect pedagogical experiences within Islamic education contexts. Data analysis was conducted thematically by identifying patterns of meaning, conceptual relationships, and recurring trends across sources. The findings indicate that the integration of a humanistic approach with strategies such as student-centered learning, contextual learning, problem-based learning, and reflective practices facilitates deeper internalization of values, characterized by active engagement, self-awareness, and authentic spiritual meaning-making among students. These findings suggest that learning processes grounded in subjective experience and empathetic relationships significantly contribute to the development of adaptive spiritual intelligence in response to contemporary challenges. Theoretically, this study reinforces the humanistic paradigm in Islamic education, while practically it offers implications for designing more reflective, contextual, and transformative learning models, as well as opening avenues for further exploration on the integration of technology and spirituality in education.